Determination of salinity tolerance limits of tilapia, Oreochromis mossambicus, for use in tuna line fishery - Fitwi, Biniam Samuel (Stellenbosch : Stellenbosch University, 2012)
Assignment (MPhil)--Stellenbosch University, 2003.